Elementary school teachers and teaching with technology - Varol, Filiz (My University, 2013)
This study aims to identify the relationship between elementary school teachers' ICT engagement with their attitudes towards technology. To this end, one hundred elementary school students were asked to fill out questionnaires related to their ICT knowledge, usage, and attitude towards technology. The results show that teachers' ICT knowledge and usage is very low. Also, their attitude toward technology is at medium level. Teachers' ICT engagement predicts their attitude towards technology and selfconfidence for teaching with technology. © The Turkish Online Journal of Educational Technology.
Keywords: Attitudes; Elementary school teachers; Self-confidence; Technology